The Autonomy and Socio-Economic Conditions of the Faroe Islands, Greenland and the Aland Islands - Leśniewski, Leszek (Studia Scandinavica, 2022)
The aim of this article is to analyse the territorial autonomy and socio-economic conditions of the Faroe Islands, Greenland and the Aland Islands. The study presents these Nordic territories in comparison to Denmark and Finland. The impact of Danish economy on the Faroe Islands and Greenland, and Finnish economy on the Aland Islands, contributed to the development of interrelations between them. The article presents the results of research analysing selected macroeconomic and social indicators in the period 2010–2020. Considering the level of preparation of the Faroe Islands, Greenland and Aland Islands for full independence, the study concludes that in political, social and economic terms, the Aland Islands are the most prepared, followed by the Faroe Islands, while Greenland is the least prepared. The aim of this article is to analyse the territorial autonomy and socio-economic conditions of the Faroe Islands, Greenland and the Aland Islands. The study presents these Nordic territories in comparison to Denmark and Finland. The impact of Danish economy on the Faroe Islands and Greenland, and Finnish economy on the Aland Islands, contributed to the development of interrelations between them. The article presents the results of research analysing selected macroeconomic and social indicators in the period 2010–2020. Considering the level of preparation of the Faroe Islands, Greenland and Aland Islands for full independence, the study concludes that in political, social and economic terms, the Aland Islands are the most prepared, followed by the Faroe Islands, while Greenland is the least prepared.